The agro-economic development of the lowland region of Lesotho - Helman, Chaim (School of Economics, 2016)
The purpose of this study is to explore the possibilities of agricultural development through the intensification of crop production in the lowland of Lesotho. The methodology used went through the following steps: a) A representative "village model" based on studies of lowland conditions was formulated. b) The alternative ways of intensifying crop production in the lowlands were studied. c) Linear programming was used in comparing the alternative ways by planning the "village model" with the objective of profit maximization. d) The planning results were analysed and conclusions were drawn. e) Organization patterns which are required for their implementation were recommended.